Smart Infusation Patient Based On Microcontroller And Ecogreen - Zaid Syahluthfy; Solly Aryza; Adi Tarigan (Sean Institute, 2021)
An infusion Patient is a device used to provide food or medicine to patients in liquid form. In some hospitals, intravenous fluids were still administered manually, patients were given intravenous fluids and medical staff needs to pay attention to the clock at the same time counted the number of fluid drops per minute. Therefore, in this study, a device was designed to control the infusion drip. Where the framework of this tool is made of aluminum, acrylic, and wooden rods, and the voltage source is an electrical circuit that is connected in parallel with a 12-volt battery. Use an LED and a photodiode to read the droplet and the tip of the droplet. The automatic mechanical drive of the system uses a servomotor. To enter the desired number of drops via the keypad will sound an alarm as an indicator that the liquid is insufficient and not dripping. The main controller is the ATMega16AVR microcontroller. The programming language used for programming is CodeVision AVR Evaluation V2.05.0. Using the above components, the tool can detect the number of droplets that can be injected with a maximum error of 4.54%. You can add sensors or change the automatic mechanism of the system for faster stability.